ATTITUDE AND LEGAL CONSCIOUSNESS OF MUSLIM FAMILIES REGARDING THE MUI FATWA ON SUPPORTING PALESTINE - Hadi, Mukhammad Nur; Anto, Abdul Haris Fitri; Ningtyas, Mega Ayu; Sholikhah, Nichatus (Indonesian Journal of Shariah and Justice, 2024)
The issuance of MUI Fatwa number 83 of 2023, addressing the Law and Support for the Palestinian Struggle, has elicited diverse reactions from the public. Some view it as a means of expressing solidarity with the Palestinian people's struggle against colonialism. In contrast, others harbor skepticism due to potential negative repercussions, especially for Muslim families targeted by the fatwa. Consequently, this study aims to assess the support of Muslim families for MUI Fatwa No. 23 of 2023, particularly those directly impacted and unaffected by the fatwa. Employing a quantitative-qualitative method, this research uses psychological and philosophical approach by utilizing attitude and Maqashid theory. The research utilized a Likert scale measuring support for the MUI fatwa, validated and tested for reliability. The scale was administered through the Google Form application in an online distribution. The study involved 176 Muslim families, encompassing both those affected and unaffected by the fatwa. Overall, the findings indicate a moderate level (mean 62,81). It covered 35,8% of the respondent's support for the MUI fatwa among Muslim families. Post hoc analysis revealed a significantly higher mean for the affective aspect (3.94) compared to the cognitive (3.75) and behavioral aspects (3.65), emphasizing the emotional nature of the support. Furthermore, a comparison of support between affected (64.02) and unaffected (62.3) families revealed an insignificant difference (p-value 0.152 > 0.05). In the perspective attitude theory, the Muslim family's response to the MUI fatwa falls within the moderate range and leans towards an emotional rather than cognitive and behavioral inclination. In the Maqashid perspective, they tend to fight for the value of human protection (hifdh an-nafs) for themselves and their families. On the one hand they also condemn Israel's crimes against Palestinians. Here it can be stated that their attitude and legal consciousness in the cognitive aspect is not comparable to the practical aspect.